A psychologist-led educational intervention results in a sustained reduction in neonatal intensive care unit infections - Hans Van, Rostenberghe; Jacki, Short; Ramli, Noraida; Tan, Beng Geok; Subramaniam, Sivasangari; Che Yaakob, Che Anuar; Othman, Azizah; Ibrahim, Nor Rosidah; Ho, Jacqueline; Mohamed, Zeehaida; Hasan, Habsah (Frontiers Media, 2014)
Even though in the corporateworld psychological science has been widely used, the formal use of evidence-based psychology in important areas of clinical medicine has been scanty at best. It was the aim of this study to determine the efficacy of a psychologist-led 2-week nurse educator training on the infection rate in the neonatal intensive care unit (NICU). Materials and methods: In 2007, six senior neonatal nurses underwent a training course focusing on the retrieval of evidence and knowledge of psychological principles that would allow them to share the evidence in such a way that evidence is effectively brought into practice.The course was led by a psychologist.The nurses created and delivered their own teaching modules, all focused on infection control. The rates of bacteremia, 2 years prior to intervention were analyzed and compared with the rate following the intervention for 3 years.